Social Displacement in The Global Era in Baek Se-Hee’s Novel - Setiowati, Titik; Thohiriyah, Thohiriyah (Language Circle: Journal of Language and Literature, 2024)
This study analyzes the phenomenon of social displacement occurs in society in the global era as reflected in Baek Se-Hee's memoir "I Want to Die but I Want to Eat Tteokbokki." The narrative describes how the main character responds to the people and environment around her reflecting social displacement. By using the theories of social displacement and the global era, this study presents the forms of the social displacement phenomenon and how society in the global era influences the social displacement phenomenon. This study is presented using a qualitative descriptive method, describing the results of the analysis by collecting data in the form of text. The results of the analysis prove that the forms of social displacement are feelings of alienation, not being recognized, and loss of identity. The impact on individuals who experience social displacement is difficulty adapting and finding social support. The global era influences the phenomenon of social displacement through industrialization and digitalization as depicted in the novel.